Strong differentiation within Diplocarpon rosae strains based on microsatellite markers and greenhouse‐based inoculation protocol on Rosa. (20th April 2020) - Marolleau, Brice; Petiteau, Aurélien; Bellanger, Marie‐Noëlle; Sannier, Mélanie; Le Pocreau, Nadège; Porcher, Laetitia; Paillard, Sophie; Foucher, Fabrice; Thouroude, Tatiana; Serres‐Giardi, Laurana; Aguileta, Gabriela; Chastellier, Annie; et al.
Abstract: The haploid ascomycete Diplocarpon rosae is the causal agent of black spot disease on roses, a widespread and devastating disease in the outdoor landscape. In this study, we established a Eurasian collection of 77 monoconidial strains of D . rosae: 50 strains collected on cultivated roses in Europe and Asia, and 27 strains on wild roses in Kazakhstan. To provide tools to describe its biology and to study its genetic diversity, we sequenced two strains of D . rosae using Illumina paired‐end technology. The genome sizes of these two strains were estimated at 31.1 and 35.2 Mb, which are two times smaller than the genome size of the unique strain previously published. A BUSCO analysis confirmed a genome duplication of the strain previously sequenced and partial gene duplication of strains analysed in this study. Using the two genome sequences, 27 polymorphic microsatellite markers were identified. Polymorphism analysis of the 77 strains revealed a strong genetic differentiation between strains from cultivated and wild roses, and a lower diversity within the fungal population from cultivated roses compared to the population from wild roses. Pathogenicity of 10 strains was evaluated on 9 rose cultivars inoculated in the greenhouse. Disease scoring allowed the classification of strains into three groups and the characterization of resistance of rose cultivars. Good correlation observed between resistance scoring in greenhouse conditions and in the field indicates that pathogenicity assays in controlled conditions could be very useful in the near future to rapidly characterize the resistance of new rose varieties to black spot disease. Abstract : A genetic diversity study of Diplocarpon rosae allowed the distinction of two groups from wild and cultivated roses. In parallel, an assay in controlled conditions was developed to characterize the pathogenicity of D. rosae strains.